The effect of the self-schedule strategy (K.W.L) on the achievement and retention of learners of the sixth grade of middle school in Misan Governorate. (Journal of the College of Basic Education, 2025)
The objective of this research is to determine the effect of the self-scheduling approach (K.W.L) on the academic performance and retention of sixth-grade middle school students in art instruction. The researcher employed the experimental research methodology to evaluate the subsequent two hypotheses:- No statistically significant differences were observed at the 0.05 significance level between the average achievement scores of the experimental group, who studied art education using the self-schedule strategy (K.W.L), and the average achievement scores of the control group, who studied the same subject through traditional methods.- No statistically significant differences (p > 0.05) exist between the average retention scores of learners in the experimental group utilising the self-schedule strategy (K.W.L) and those in the control group studying the same material through traditional methods. This study pertains exclusively to sixth-grade middle school students for the academic year 2023-2024 and focusses on art education subjects, in accordance with the methodological terminology established by the Ministry of Education, Department of Curricula. The researcher developed an objective achievement test based on derived behavioural objectives. The test's validity was confirmed by a panel of experts, and its reliability was established through a test-retest method, achieving a stability coefficient of 80.0. Following the administration of the finalised test, data were collected and statistically analysed. The research findings indicated that the self-schedule strategy (K.W.L) was effective in enhancing the collection and retention of knowledge among sixth-grade middle school students in art education. Consequently, the researcher provided a series of recommendations and suggestions based on the results